Ukraine and the legal accountability of Russia : the emergence of a new global order - Dutton, Yvonne; Scharf, Michael P., 1963-; Sterio, Milena; Williams, Paul R., 1965- (Routledge, 2026)
"This book explains how the response to Russia's 2022 invasion of Ukraine has transformed international law. It analyzes the significance of the resurrection of the UN General Assembly's Uniting for Peace mechanism, the insertion of the International Criminal Court into world politics at the highest level, and the creation of new types of investigatory mechanisms and tribunals. It explores ground breaking developments related to war reparations, the crime of aggression and attacks on the environment. And it makes the case that, rather than personifying the failure of international law, the Russia-Ukraine war has demonstrated its continuing relevance and resilience in surprising ways. This work will be compelling reading for academics, researchers and policy-makers working in the areas of International Criminal Law, International Humanitarian Law and the Law of Armed Conflict"--